Música negra en los Andes colombianos. Historia y política de las sonoridades Afro en Girardota-Antioquia (Orfeu, 2018)
This paper aims to offer a reflection on the artistic manifestations of an Afro-descendant community in the Colombian department of Antioquia. From an interdisciplinary fieldwork, we explore with special attention the string music that has made visible in the regional, national and international scope, the interpreters and composers of this community. The contribution of the research consigned in this text is to expose the preponderant role of these manifestations in the ethnic affirmation of the group, where unlike other Afro populations of the continent, there is no musical tradition of percussion. This research concludes that the studied group affirms its identity from the interpretation of music and other practices that are associated with an Iberian origin, but that in the local context have been appropriate and incorporated as part of its legacy and tradition.
Keywords: afro colombian music; ethnicity; Girardota; Antioquia